Carbon nanotube, dispersion liquid thereof, resin composition thereof, composite material slurry, electrode film, nonaqueous electrolyte secondary battery, and vehicle
By using carbon nanotubes with specific characteristics, the problem of insufficient dispersion of carbon nanotube dispersion in the prior art is solved, and an electrode film with excellent conductivity and adhesion and a nonaqueous electrolyte secondary battery are realized, thereby improving the rate and circulation characteristics of the battery.
Patent Information
- Application Number
- CN202411837240.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-04
- Filing Date
- 2021-07-07
- Publication Date
- 2025-03-28
AI Technical Summary
It is difficult to obtain a high concentration and uniformly dispersed carbon nanotube dispersion in the prior art, resulting in insufficient conductivity and cycle life of lithium-ion secondary batteries.
By using a specific carbon nanotube, its pH is 8.0 to 10.0, its BET specific surface area is 200m2/g to 800m2/g, and the specific fiber length and specific surface area relationship are met, an electrode film and a nonaqueous electrolyte secondary battery with excellent conductivity and adhesion are formed.
The electrode film with excellent conductivity and adhesion is realized, and the rate characteristics and cycle characteristics of the nonaqueous electrolyte secondary battery are improved, and it is suitable for secondary batteries of various purposes.
Smart Images

Figure CN119725534A_ABST
Abstract
Description
[0001] The present invention is a divisional application of the invention patent application with application number 202180044269.8 filed on July 7, 2021, and invention name "Carbon nanotubes, their dispersions, their resin compositions, composite material slurries, electrode films, non-aqueous electrolyte secondary batteries and vehicles". Technical Field
[0002] Embodiments of the present invention relate to carbon nanotubes and uses thereof. More specifically, embodiments of the present invention relate to carbon nanotubes, and carbon nanotube dispersions, resin compositions, composite material slurries, electrode films, nonaqueous electrolyte secondary batteries, and vehicles using the carbon nanotubes. Background Art
[0003] With the popularity of electric vehicles and the miniaturization, lightness and high performance of portable devices, there is a demand for a secondary battery with high energy density, and further a demand for a high capacity of the secondary battery. In this context, due to the characteristics of high energy density and high voltage, non-aqueous electrolyte secondary batteries using non-aqueous electrolytes, especially lithium-ion secondary batteries, are used in a large number of devices.
[0004] As the negative electrode material used in these lithium ion secondary batteries, a carbon material represented by graphite having a low potential close to lithium (Li) and a large charge and discharge capacity per unit mass is used. However, these electrode materials are used at a level close to the theoretical value of the charge and discharge capacity per mass, and the energy density per mass of the battery is close to the limit. Therefore, in order to improve the utilization rate as an electrode, attempts are being made to reduce the amount of conductive additives or binders that do not contribute to the discharge capacity.
[0005] As conductive aids, carbon black, Ketjen black, fullerene, graphene, fine carbon materials, etc. are used. In particular, carbon nanotubes, which are a kind of fine carbon fibers, are used in large quantities. For example, by adding carbon nanotubes to graphite or silicon negative electrodes, the electrode resistance is reduced, or the load resistance of the battery is improved, or the strength of the electrode is increased, or the expansion and contraction of the electrode is increased, thereby increasing the cycle life of the lithium secondary battery (for example, refer to Patent Document 1, Patent Document 2, and Patent Document 3). In addition, research on reducing electrode resistance by adding carbon nanotubes to the positive electrode has also been conducted (for example, refer to Patent Document 4). Among them, multilayer carbon nanotubes with an outer diameter of 10nm to several 10nm are relatively cheap and can be expected to be practical.
[0006] If the carbon nanotube with a small average outer diameter is used, a conductive network can be formed efficiently in a small amount, so the amount of the conductive aid contained in the positive electrode and the negative electrode of the lithium ion secondary battery can be reduced. In addition, it is known that the same effect is also obtained when the carbon nanotube with a large fiber length is used (for example, with reference to patent documentation 6). However, the cohesive force of the carbon nanotube with these characteristics is strong and difficult to disperse. Therefore, it is impossible to obtain a carbon nanotube dispersion with sufficient dispersibility.
[0007] Therefore, methods for dispersing and stabilizing carbon nanotubes using various dispersants have been proposed. For example, dispersion in water and N-methyl-2-pyrrolidone (NMP) using polymer dispersants such as water-soluble high molecular weight polyvinyl pyrrolidone has been proposed (see Patent Document 4 and Patent Document 5). However, in Patent Document 4, an electrode made using carbon nanotubes with an outer diameter of 10nm to 150nm was evaluated, but there was a problem of high electrode resistance. In Patent Document 5, a dispersion liquid using single-layer carbon nanotubes was studied, but it was difficult to disperse the carbon nanotubes in a solvent at a high concentration. In Patent Document 7, a carbon nanotube dispersion liquid containing a triazine derivative having an acidic functional group was proposed, but there was a problem that the carbon nanotubes were easily agglomerated when the carbon nanotubes were dispersed in an aqueous liquid medium. In Patent Document 8, dispersion using two-layer carbon nanotubes was studied. However, oxidation treatment or ultrasonic dispersion of the carbon nanotubes is required, and it is difficult to disperse the carbon nanotubes in a solvent at a high concentration. In Patent Document 9, in order to prepare carbon nanotubes suitable as a conductive aid for lithium ion secondary batteries, a ball mill type disperser is used to prepare a carbon nanotube dispersion in which carbon nanotubes with an outer diameter of 150 nm are dispersed into about 2 μm to 7 μm. However, in order to obtain sufficient conductivity, a large amount of carbon nanotubes must be used.
[0008] Therefore, obtaining a carbon nanotube dispersion in which carbon nanotubes having a small outer diameter and a large fiber length are uniformly dispersed in a dispersion medium at a high concentration is an important issue for expanding the application.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Laid-Open No. 4-155776
[0012] Patent Document 2: Japanese Patent Laid-Open No. 4-237971
[0013] Patent Document 3: Japanese Patent Application Publication No. 2004-178922
[0014] Patent Document 4: Japanese Patent Application Publication No. 2011-70908
[0015] Patent Document 5: Japanese Patent Application Publication No. 2005-162877
[0016] Patent Document 6: Japanese Patent Application Publication No. 2012-221672
[0017] Patent Document 7: Japanese Patent Application Publication No. 2020-11872
[0018] Patent Document 8: Japanese Patent Application Publication No. 2010-254546
[0019] Patent Document 9: Japanese Patent Application Publication No. 2014-182892 Summary of the invention
[0020] Problems to be solved by the invention
[0021] In view of the above situation, one embodiment of the present invention provides a carbon nanotube, which can be preferably used as a conductive auxiliary agent and has excellent dispersibility. In addition, another embodiment of the present invention provides a carbon nanotube, a carbon nanotube dispersion, a carbon nanotube resin composition and a composite material slurry with high dispersibility in order to obtain an electrode film with high adhesion and conductivity. Furthermore, another embodiment of the present invention provides a non-aqueous electrolyte secondary battery with excellent rate characteristics and cycle characteristics.
[0022] Technical means of solving problems
[0023] The inventors of the present invention have conducted intensive research to solve the above-mentioned problems. As a result, the inventors have found that the desired properties can be obtained by using carbon nanotubes having a pH of 8.0 to 10.0 and a Brunauer-Emmett-Teller (BET) specific surface area of 200 m 2 / g~800m 2 / g, the fiber length of the carbon nanotube (nm) is set to Y, the BET specific surface area of the carbon nanotube (m 2 / g) is set as X, Y = -aX + b (a, b are constants, 2.2 ≤ a ≤ 3.5, 2300 ≤ b ≤ 5000). That is, by using the specific carbon nanotubes, it is easy to obtain an electrode film with excellent conductivity and adhesion, and a non-aqueous electrolyte secondary battery with excellent rate characteristics and cycle characteristics. Based on the above findings, the inventors and others completed the present invention.
[0024] That is, one embodiment of the present invention relates to a carbon nanotube characterized by satisfying the following (1) to (3).
[0025] (1) The pH of the carbon nanotube aqueous dispersion is 8.0 to 10.0.
[0026] (2) The BET specific surface area of carbon nanotubes is 200 m 2 / g~800m 2 / g.
[0027] (3) When the fiber length (nm) of the carbon nanotube is denoted as Y and the BET specific surface area (m 2 / g) is set as X, Y=-aX+b (a and b are constants, 2.2≦a≦3.5, 2300≦b≦5000).
[0028] The carbon nanotubes of the embodiment described above preferably have a Raman spectrum of 1560 cm -1 ~1600cm -1 The maximum peak intensity in the range of 1310 cm -1 ~1350cm -1 When the maximum peak intensity in the range of is set to D, the G / D ratio is 0.5 to 4.5.
[0029] In the above embodiment, the average outer diameter of the carbon nanotubes is preferably 5 nm to 20 nm.
[0030] In the above embodiment, the volume resistivity of the carbon nanotubes is preferably 1.0×10 -2 Ω·cm~3.0×10 -2 Ω·cm.
[0031] Another embodiment of the present invention relates to a carbon nanotube dispersion liquid, comprising the carbon nanotubes of the above embodiment, a dispersant, and an aqueous liquid medium.
[0032] In the carbon nanotube dispersion of the above embodiment, the complex elastic modulus of the carbon nanotube dispersion is preferably 1 Pa to 100 Pa.
[0033] In the carbon nanotube dispersion of the embodiment, it is preferred that the product (X×Y) of the complex elastic modulus X (Pa) and the phase angle Y (°) of the carbon nanotube dispersion is 100 or more and 1,500 or less.
[0034] In the carbon nanotube dispersion of the above embodiment, it is preferred that the dispersant be contained in an amount of 10 to 100 parts by mass based on 100 parts by mass of the carbon nanotubes.
[0035] The pH of the carbon nanotube dispersion liquid of the above embodiment is preferably 7-11.
[0036] In the carbon nanotube dispersion of the embodiment, the 50% particle size (D50) calculated by laser diffraction particle size distribution measurement is preferably 1 μm to 20 μm.
[0037] The carbon nanotube dispersion of the embodiment is preferably a dispersion containing 0.4 parts by mass or more and 2.5 parts by mass or less of carbon nanotubes per 100 parts by mass of the carbon nanotube dispersion, and when the viscosity of the carbon nanotube dispersion measured at 6 rpm using a B-type viscometer is set to α and the viscosity of the carbon nanotube dispersion measured at 60 rpm is set to β, α / β satisfies 2.0≦α / β≦6.0.
[0038] Another embodiment of the present invention relates to a carbon nanotube resin composition including the carbon nanotube dispersion of the embodiment and a binder resin.
[0039] In the carbon nanotube resin composition of the embodiment, the binder resin preferably includes at least one selected from the group consisting of carboxymethyl cellulose, styrene butadiene rubber, and polyacrylic acid.
[0040] Another embodiment of the present invention relates to a composite material slurry, comprising the carbon nanotube resin composition of the embodiment and an active substance.
[0041] Another embodiment of the present invention relates to an electrode film, which is a coating film of the composite material slurry of the above embodiment.
[0042] Another embodiment of the present invention relates to a nonaqueous electrolyte secondary battery including a positive electrode, a negative electrode, and an electrolyte, wherein at least one of the positive electrode or the negative electrode of the nonaqueous electrolyte secondary battery includes the electrode film of the embodiment.
[0043] Another embodiment of the present invention is directed to a nonaqueous electrolyte secondary battery including the carbon nanotube of the embodiment.
[0044] Another embodiment of the present invention relates to a vehicle including the nonaqueous electrolyte secondary battery of the embodiment.
[0045] The disclosure of this application is related to the subject matter described in Japanese Patent Application No. 2020-116805 filed on July 7, 2020 and Japanese Patent Application No. 2021-034455 filed on March 4, 2021, and all of these disclosures are incorporated herein by reference.
[0046] Effects of the Invention
[0047] According to an embodiment of the present invention, by using specific carbon nanotubes that meet specific necessary conditions related to pH, BET surface area and average fiber length, a resin composition, composite material slurry, and electrode film with excellent conductivity and adhesion can be obtained. In addition, a non-aqueous electrolyte secondary battery with excellent rate characteristics and cycle characteristics can be obtained. According to the present invention, a carbon nanotube and a carbon nanotube dispersion liquid that can be preferably used in various application fields such as vehicles requiring excellent non-aqueous secondary electrolyte secondary batteries can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a graph showing the relationship between the BET specific surface area and the fiber length of CNT for carbon nanotubes (CNT) produced in Examples of the present invention and carbon nanotubes (CNT) used in Comparative Examples and Reference Examples. DETAILED DESCRIPTION
[0049] Hereinafter, as an example of an embodiment of the present invention, carbon nanotubes, carbon nanotube dispersions, resin compositions, composite material slurries, electrode films obtained by forming the composite material slurries into films, and nonaqueous electrolyte secondary batteries are described in detail. However, the present invention is not limited to the following descriptions, but includes various embodiments.
[0050] <Carbon Nanotube>
[0051] The carbon nanotube as one embodiment of the present invention has a shape in which a plane of graphite is wound into a cylindrical shape. Single-layer carbon nanotubes may be mixed in the carbon nanotubes. Single-layer carbon nanotubes have a structure in which one layer of graphite is wound. Multi-layer carbon nanotubes have a structure in which two or more layers of graphite are wound. In addition, the side wall of the carbon nanotube may not be a graphite structure. For example, a carbon nanotube having a side wall having an amorphous structure may also be used as the carbon nanotube.
[0052] The shape of the carbon nanotubes in this embodiment is not limited. As a shape, for example, it can be various shapes including needle-shaped, cylindrical tube-shaped, fishbone-shaped (fishbone or cup stacked type), and coil-shaped. Among them, in this embodiment, the shape of the carbon nanotube is preferably needle-shaped or cylindrical tube-shaped. The carbon nanotube can be a single shape or a combination of two or more shapes.
[0053] As the form of the carbon nanotube of this embodiment, for example, graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes and carbon nanofibers can be listed. However, it is not limited to these. The carbon nanotube can also have these forms alone or in a form of a combination of two or more.
[0054] The carbon nanotubes of the present embodiment have a pH of 8.0 to 10.0 as an aqueous dispersion, and more preferably 8.5 to 9.5. Here, the pH of the aqueous dispersion of carbon nanotubes is a value obtained by measuring the pH of an aqueous dispersion prepared by adding 1 part by mass of carbon nanotubes to 100 parts by mass of ion exchange water and then dispersing the carbon nanotubes using an ultrasonic homogenizer.
[0055] In one embodiment, the aqueous dispersion used in the specific case may be, for example, an aqueous dispersion prepared in the following manner. First, 2 g of carbon nanotubes and 200 mL of ion exchange water are measured respectively. Then, they are dispersed for 1 minute using an ultrasonic homogenizer under ice bath cooling. Then, the mixture is allowed to stand at room temperature (25° C.) for more than 1 hour.
[0056] During the measurement, it is preferred to treat the aqueous dispersion by centrifugation or a filter, and separate the carbon nanotubes (CNT) from the water and measure. The carbon nanotubes having a pH of 8.0 to 10.0 in the aqueous dispersion have high wettability to a water-soluble liquid medium represented by water or NMP. Therefore, when the pH of the aqueous dispersion of CNT is within the range, it is easy to obtain excellent dispersibility in the water-soluble liquid medium. Therefore, when the pH of the aqueous dispersion is within the range, it can be preferably used as a carbon nanotube for a non-aqueous electrolyte secondary battery.
[0057] The BET specific surface area of the carbon nanotubes in this embodiment can be 200 m 2 / g~800m 2 In one embodiment, the BET specific surface area is more preferably 250 m 2 / g~750m 2 / g, and more preferably 300m 2 / g~700m 2 / g.
[0058] When using a BET specific surface area of 200m 2 In the case of carbon nanotubes having a BET specific surface area of 800 m 2 In the case of carbon nanotubes with a BET specific surface area of 200 m 2 / g~800m 2 When the content of MgO is within the range of MgO / g, a developed conductive network is easily formed, thereby improving the conductivity of the electrode film.
[0059] Although not particularly limited, in one embodiment, the BET specific surface area may be 200 m 2 / g~400m 2 / g, also 401m 2 / g~600m 2 / g, also 601m 2 / g~800m 2 / g.
[0060] The average fiber length of the carbon nanotubes of this embodiment is preferably 700 nm or more, more preferably 1000 nm or more. In one embodiment, the average fiber length may be 1200 nm or more. On the other hand, the average fiber length is preferably less than 5000 nm, more preferably less than 4000 nm. In one embodiment, the average fiber length may also be less than 2000 nm.
[0061] When using carbon nanotubes with an average fiber length of 700 nm or more, there is a tendency to easily improve the expansion and contraction properties and cycle characteristics of the electrode. In addition, when using carbon nanotubes with an average fiber length of less than 5000 nm, there is a tendency to easily suppress the occurrence of aggregation or breakage of the carbon nanotubes, thereby easily providing an electrode with excellent conductivity.
[0062] In one embodiment, the average fiber length of the carbon nanotubes is more preferably 1000 nm or more and less than 5000 nm, and may be 1000 nm or more and less than 2000 nm, or 2000 nm or more and less than 4000 nm. In another embodiment, the average fiber length of the carbon nanotubes is more preferably 1000 nm or more and less than 5000 nm, and may be 1500 nm or more and less than 4000 nm.
[0063] As described above, the average fiber length and BET specific surface area of carbon nanotubes affect the conductivity of the electrode and the rate characteristics and cycle characteristics of the battery, so it is preferably selected appropriately within the numerical range. In contrast, in the research of the present inventors and others, it was found that the average fiber length and BET specific surface area of carbon nanotubes can be specified by the following formula.
[0064] That is, the carbon nanotubes of the present embodiment are denoted by the average fiber length (nm) of the carbon nanotubes and the BET specific surface area (m 2 / g) is set to X, the following (Formula 1) is satisfied.
[0065] (Formula 1) Y = -aX + b
[0066] In Formula 1, a and b are constants, 2.2≦a≦3.5, 2300≦b≦5000, preferably 2600≦b≦4800.
[0067] The carbon nanotubes of the present embodiment further preferably satisfy the following (Formula 2).
[0068] (Formula 2) Y = -aX + b
[0069] In formula 2, a and b are constants, 1.2≦a≦3.5, 2600≦b≦4000.
[0070] As described above, the above formulas 1 and 2 represent the carbon nanotubes with the average fiber length (nm) of the carbon nanotubes as Y, the BET specific surface area (m 2 The correlation between the average fiber length [Y] and the BET specific surface area [X] means that there are constants a and b that are equal on both sides of the equation for each value of the average fiber length [Y] and the BET specific surface area [X].
[0071] In one embodiment, a may be a constant of 1.2 to less than 2.2, or a constant of 2.2 to 3.5. b may be a constant of 2300 to less than 3300, or a constant of 3300 to 5000.
[0072] When using carbon nanotubes whose constant a and constant b fall within the above ranges, characteristics such as high output and long life of the battery can be easily obtained.
[0073] In one embodiment, the average fiber length (nm) of the carbon nanotubes is denoted as Y, the BET specific surface area (m 2 When x is X, it preferably satisfies -3.5X+2300<Y or Y<2.2X+5000. The carbon nanotube more preferably satisfies the following (Formula 3).
[0074] (Formula 3)
[0075] -3.5X+2300<Y<-2.2X+5000
[0076] In one embodiment, the carbon nanotubes further preferably satisfy the following (Formula 3').
[0077] (Formula 3')
[0078] -3.5X+2600<Y<-2.2X+4800
[0079] As an example of the carbon nanotube satisfying the above (Formula 1), the following carbon nanotubes (CNTs) produced in the examples described later can be cited.
[0080] CNT (A): BET specific surface area is 680 (m 2 / g), the average fiber length is 1100nm
[0081] CNT(B): BET specific surface area is 580(m 2 / g), the average fiber length is 1600nm
[0082] CNT(C): BET specific surface area is 500(m 2 / g), the average fiber length is 1500nm
[0083] CNT(D): BET specific surface area is 430(m 2 / g), the average fiber length is 1700nm
[0084] CNT(E): BET specific surface area is 330(m 2 / g), the average fiber length is 1800nm
[0085] CNT(F): BET specific surface area is 220(m 2 / g), the average fiber length is 2300nm
[0086] CNT(G): BET specific surface area is 710(m 2 / g), the average fiber length is 2400nm
[0087] CNT(H): BET specific surface area is 600(m 2 / g), the average fiber length is 2800nm
[0088] CNT(I): BET specific surface area is 530(m 2 / g), the average fiber length is 2600nm
[0089] CNT(J): BET specific surface area is 440(m 2 / g), the average fiber length is 3000nm
[0090] CNT(K): BET specific surface area is 360(m 2 / g), the average fiber length is 4000nm
[0091] CNT(L): BET specific surface area is 250(m 2 / g), the average fiber length is 3800nm
[0092] CNT(GA): BET specific surface area is 680(m 2 / g), the average fiber length is 1800nm
[0093] CNT(IA): BET specific surface area is 510(m 2 / g), the average fiber length is 2000nm
[0094] CNT(Q): BET specific surface area is 720(m 2 / g), the average fiber length is 3100nm
[0095] CNT(R): BET specific surface area is 620(m 2 / g), the average fiber length is 700nm
[0096] CNT(S): BET specific surface area is 550(m 2 / g), the average fiber length is 900nm
[0097] However, the carbon nanotubes of the present embodiment are not limited to these, and any carbon nanotubes may be used as long as they satisfy all of the above-described requirements (1) to (3).
[0098] The carbon nanotubes are evaluated by the G / D ratio (peak ratio of the G-band to the D-band). The G / D ratio of the carbon nanotubes of this embodiment is obtained by Raman spectroscopy. In the Raman spectrum, the carbon nanotubes of this embodiment have a peak at 1560 cm -1 ~1600cm -1 The maximum peak intensity in the range is set as G, and the peak intensity at 1310 cm -1 ~1350cm -1 When the maximum peak intensity in the range is defined as D, the G / D ratio is preferably 0.5 to 10. The G / D ratio is more preferably 0.5 to 4.5, and even more preferably 0.5 to 2.0.
[0099] The average outer diameter of the carbon nanotubes of the present embodiment is preferably 5 nm to 25 nm, more preferably 5 nm to 20 nm, and even more preferably 5 nm to 15 nm.
[0100] The outer diameter and average outer diameter of the carbon nanotubes of the present embodiment are calculated as follows. First, the carbon nanotubes are observed and photographed using a transmission electron microscope. Next, 300 carbon nanotubes are randomly selected from the observed photographs, and their outer diameters are measured. Next, the average outer diameter (nm) of the carbon nanotubes is calculated as the number average of the outer diameters.
[0101] The number of layers of the carbon nanotubes in the carbon nanotube of the present embodiment is preferably 3 or more and 30 or less, more preferably 3 or more and 20 or less, and still more preferably 3 or more and 10 or less.
[0102] The carbon nanotubes of this embodiment preferably have a peak at a diffraction angle of 2θ=25°±2° when performing powder X-ray diffraction analysis, and the half-value width of the peak is preferably greater than 2° and less than 6°, more preferably greater than 2.5° and less than 6°, and further preferably greater than 3° and less than 6°.
[0103] The volume resistivity of the carbon nanotubes of this embodiment is preferably 1.0×10 -2 Ω·cm~3.0×10-2 Ω·cm, more preferably 1.0×10 -2 Ω·cm~2.0×10 -2 Ω·cm. The volume resistivity of the carbon nanotubes can be measured using a powder resistivity measuring device (Mitsubishi Chemical Analytech Co., Ltd.: Loresta GP Powder Resistivity Measuring System MCP-PD-51).
[0104] The carbon purity of the carbon nanotubes of this embodiment is represented by the content (%) of carbon atoms in the carbon nanotubes. The carbon purity is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more relative to 100% by mass of the carbon nanotubes.
[0105] The amount of metal contained in the carbon nanotubes of the present embodiment is preferably less than 10% by mass, more preferably less than 5% by mass, and further preferably less than 2% by mass relative to 100% by mass of the carbon nanotubes. Examples of the metal contained in the carbon nanotubes include metals or metal oxides used as catalysts when synthesizing carbon nanotubes. Specifically, examples include metals such as cobalt, nickel, aluminum, magnesium, silicon dioxide, manganese, or molybdenum, metal oxides, and composite oxides thereof.
[0106] The carbon nanotubes of this embodiment are usually present in the form of secondary particles. The shape of the secondary particles can be, for example, a state in which carbon nanotubes of general primary particles are intricately entangled with each other. It can also be an aggregate of carbon nanotubes arranged in a straight line. The secondary particles of the aggregate of linear carbon nanotubes are easier to loosen than the form in which carbon nanotubes are entangled with each other. In addition, if the linear form is better in dispersibility than the form in which the carbon nanotubes are entangled with each other, it can be preferably used as a carbon nanotube.
[0107] The carbon nanotubes of this embodiment may be surface-treated carbon nanotubes. Alternatively, the carbon nanotubes may be carbon nanotube derivatives endowed with functional groups represented by carboxyl groups. Alternatively, carbon nanotubes containing organic compounds, metal atoms, or substances represented by fullerenes may be used.
[0108] The carbon nanotubes of this embodiment may be carbon nanotubes produced by any method. Carbon nanotubes can generally be produced by laser ablation, arc discharge, thermal chemical vapor deposition (CVD), plasma CVD, and combustion, but are not limited thereto. For example, carbon nanotubes can be produced by contacting a carbon source with a catalyst at 500°C to 1000°C in an environment where the oxygen concentration is less than 1% by volume. The carbon source may be at least one of a hydrocarbon and an alcohol.
[0109] Any known raw material can be used as the raw material gas of the carbon source of the carbon nanotubes. For example, hydrocarbons represented by methane, ethylene, propane, butane and acetylene, carbon monoxide, and alcohols can be used as raw material gases containing carbon, but they are not limited to these. In particular, from the perspective of ease of use, it is desirable to use at least one of hydrocarbons and alcohols as the raw material gas.
[0110] <Carbon Nanotube Dispersion Liquid>
[0111] The carbon nanotube dispersion liquid as one embodiment of the present invention includes carbon nanotubes, a dispersant, and an aqueous liquid medium, which will be described in detail below.
[0112] (Dispersant)
[0113] The dispersant of the present embodiment is not particularly limited as long as it can stabilize the dispersion of carbon nanotubes. For example, a surfactant or a resin-type dispersant can be used. Surfactants are mainly classified into anionic, cationic, nonionic and amphoteric. A preferred type of dispersant can be used in a preferred amount according to the characteristics required for the dispersion of carbon nanotubes.
[0114] When anionic surfactants are selected, their types are not particularly limited. Specifically, fatty acid salts, polysulfonates, polycarboxylates, alkyl sulfate ester salts, alkyl aryl sulfonates, alkyl naphthalene sulfonates, dialkyl sulfonates, dialkyl sulfosuccinates, alkyl phosphates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkyl aryl ether sulfates, naphthalenesulfonic acid formalin condensates, polyoxyethylene alkyl phosphoric acid sulfonates, glyceryl borate fatty acid esters and polyoxyethylene glycerol fatty acid esters can be listed, but they are not limited to these. Furthermore, specifically, sodium dodecylbenzene sulfonate, sodium laurate sulfate, sodium polyoxyethylene lauryl ether sulfate, polyoxyethylene nonylphenyl ether sulfate salts and sodium salts of β-naphthalenesulfonic acid formalin condensates can be listed, but they are not limited to these.
[0115] In addition, as cationic surfactants, there are alkylamine salts and quaternary ammonium salts. Specifically, stearylamine acetate, trimethyl coconut oil ammonium chloride, trimethyl tallow ammonium chloride, dimethyl dioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl pyridinium bromide, 4-alkyl mercaptopyridine, poly (vinyl pyridine) - dodecyl bromide and dodecyl benzyl triethyl ammonium chloride can be listed, but it is not limited to these. In addition, as amphoteric surfactants, aminocarboxylates can be listed, but it is not limited to these.
[0116] In addition, as nonionic surfactants, polyoxyethylene alkyl ethers, polyoxyalkylene derivatives, polyoxyethylene phenyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters and alkyl allyl ethers can be listed, but they are not limited to these. Specifically, polyoxyethylene lauryl ether, sorbitan fatty acid esters and polyoxyethylene octyl phenyl ether can be listed, but they are not limited to these.
[0117] The selected surfactant is not limited to a single surfactant. Therefore, two or more surfactants can be used in combination. For example, a combination of anionic surfactant and nonionic surfactant, or a combination of cationic surfactant and nonionic surfactant can be used. The blending amount at this time is preferably set to a preferred blending amount relative to each surfactant component. As a combination, a combination of anionic surfactant and nonionic surfactant is preferred. The anionic surfactant is preferably a polycarboxylate. The nonionic surfactant is preferably polyoxyethylene phenyl ether.
[0118] In addition, as the resin type dispersant, specifically, cellulose derivatives (cellulose acetate, cellulose acetate butyrate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, etc.), polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polyacrylonitrile polymers, etc. are listed. Methyl cellulose, ethyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polyacrylonitrile polymers are particularly preferred. The molecular weight of the resin type dispersant is preferably 10,000 to 150,000, and more preferably 10,000 to 100,000.
[0119] In addition, it is preferred to add an amine compound or an inorganic base in addition to adding a dispersant. As the amine compound, a first amine (primary amine), a second amine (secondary amine), and a third amine (tertiary amine) are used, and ammonia or quaternary ammonium compounds are not included. In addition to monoamines, amine compounds such as diamines, triamines, and tetramines having multiple amino groups in the molecule can also be used. Specifically, for example, aliphatic primary amines such as methylamine, ethylamine, butylamine, and octylamine, aliphatic secondary amines such as dimethylamine, diethylamine, and dibutylamine, aliphatic tertiary amines such as trimethylamine, triethylamine, and dimethyloctylamine, alanine, methionine, proline, serine, asparagine, glutamine, lysine, arginine, histidine, aspartic acid, glutamic acid, cysteine, dimethylaminoethanol, monoethanolamine, diethanolamine, methylethanolamine, triethanolamine, alkanolamines such as triethanolamine, hexamethylenetetramine, morpholine, piperidine, etc. can be listed, but it is not limited to these. Examples of the inorganic base include alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkaline earth metal carbonates, alkali metal phosphates, alkaline earth metal phosphates, and the like.
[0120] In addition to the dispersant, a defoaming agent may be added. Any commercially available defoaming agent, wetting agent, hydrophilic organic solvent, water-soluble organic solvent, etc., may be used as long as it has a defoaming effect. One type may be used alone or in combination of two or more types.
[0121] For example, alcohols include ethanol, propanol, isopropanol, butanol, octyl alcohol, hexadecyl alcohol, acetylene alcohol, ethylene glycol monobutyl ether, methyl cellosolve, butyl cellosolve, propylene glycol monomethyl ether, acetylene glycol, polyoxyalkylene glycol, propylene glycol, and other glycols; fatty acid esters include diethylene glycol laurate, glyceryl monoricinoleate, alkenyl succinic acid derivatives, sorbitan monolaurate, sorbitan trioleate, polyoxyethylene monolaurate, sorbitan trioleate ... Lauric acid ester, polyoxyethylene sorbitan monolaurate, natural wax, etc., amide series: polyoxyalkylene amide, acrylate polyamine, etc., phosphate ester series: tributyl phosphate, sodium octyl phosphate, etc., metal soap series: aluminum stearate, calcium oleate, etc., oil series: animal and vegetable oils, sesame oil, castor oil, etc., mineral oil series: kerosene, paraffin, etc., silicone series: dimethyl silicone oil, silicone cream, silicone emulsion, organic modified polysiloxane, fluorosilicone oil, etc.
[0122] (Aqueous liquid medium)
[0123] The aqueous liquid medium of the present embodiment is not particularly limited as long as it can disperse carbon nanotubes. For example, it is preferably a mixed solvent containing water and / or any one of water-soluble organic solvents, or two or more, and more preferably containing water. In the case of containing water, it is preferably 95 parts by mass or more relative to the whole solvent, and further preferably 98 parts by mass or more.
[0124] As the water-soluble organic solvent, the following can be used: alcohols (methanol, ethanol, propanol, isopropanol, butanol, isobutanol, sec-butanol, tert-butanol, benzyl alcohol, etc.), polyols (ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, butanediol, hexanediol, pentanediol, glycerol, hexanetriol, thiodiglycol, etc.), polyol ethers (ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, etc.), Ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, ethylene glycol monomethyl ether acetate, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, ethylene glycol monophenyl ether, propylene glycol monophenyl ether, etc.), amines (ethanolamine, diethanolamine, triethanolamine, N-methyldiethanolamine, N -ethyldiethanolamine, morpholine, N-ethylmorpholine, ethylenediamine, diethylenediamine, triethylenetetramine, tetraethylenepentamine, polyethyleneimine, pentamethyldiethylenetriamine, tetramethylpropylenediamine, etc.), amide series (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclic series (cyclohexylpyrrolidone, 2-oxazolidinone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc.), sulfoxide series (dimethyl sulfoxide, etc.), sulfone series (hexamethylphosphoric acid triamide, cyclopentane sulfone, etc.), lower ketone series (acetone, methyl ethyl ketone, etc.), as well as tetrahydrofuran, urea, acetonitrile, etc.
[0125] (Characteristics of Carbon Nanotube Dispersion Liquid)
[0126] The complex elastic modulus of the carbon nanotube dispersion of the present embodiment is preferably 1 Pa to 100 Pa, more preferably 3 Pa to 70 Pa, and further preferably 5 Pa to 50 Pa. In addition, the phase angle is preferably 5° to 60°, more preferably 5° to 40°, and further preferably 10° to 35°. The complex elastic modulus and phase angle of the carbon nanotubes can be evaluated by dynamic viscoelasticity measurement.
[0127] The complex elastic modulus represents the hardness of the CNT dispersion. The better the dispersibility of the carbon nanotubes, the lower the viscosity of the CNT dispersion, and the smaller the complex elastic modulus. However, in the case where the fiber length of the carbon nanotubes is large, even when the carbon nanotubes are uniformly and stably scattered in the medium, since the carbon nanotubes themselves have structural viscosity, the complex elastic modulus sometimes also becomes a high numerical value. In addition, the phase angle refers to the phase shift of the stress wave when the strain given to the CNT dispersion is set to a sine wave, that is, the ease of flow of the dispersion. If it is a pure elastic body, it becomes a sine wave with the same phase as the strain given, so the phase angle is 0 °. On the other hand, if it is a pure viscous body, it becomes a stress wave that advances 90 °. For a general viscoelasticity measurement sample, it becomes a sine wave with a phase angle greater than 0 ° and less than 90 °. If the dispersibility of the CNT in the CNT dispersion is good, the phase angle is close to 90 ° of the pure viscous body. However, similar to the complex elastic modulus, when the carbon nanotubes themselves have structural viscosity, the phase angle may sometimes be a low value even when the conductive material is uniformly and stably dispersed in the medium. The carbon nanotubes in the carbon nanotube dispersion within the above range have good dispersed particle size and dispersibility, and are suitable as a carbon nanotube dispersion for non-aqueous electrolyte secondary batteries.
[0128] The complex elastic modulus and phase angle of the carbon nanotube dispersion are determined by the dispersibility of the carbon nanotubes in the carbon nanotube dispersion, the entanglement of the carbon nanotubes and the dispersant, or the influence of their intermolecular forces, so if the complex elastic modulus X (Pa) and the phase angle Y (°) are set to the preferred range and their product (X×Y) is greater than 100 and less than 1,500, a carbon nanotube dispersion with excellent dispersion stability can be obtained, and an excellent conductive network can be formed, thereby obtaining an electrode film with very good conductivity.
[0129] In addition, when the weight average molecular weight of the dispersant is 10,000 to 150,000, although its own viscoelasticity is small, as long as the product (X×Y) of the complex elastic modulus X (Pa) and the phase angle Y (°) when the carbon nanotube dispersion is made is 100 or more and 1,500 or less, it will be sufficient. It is believed that such a dispersant can act as a thickener or binder used in an electrode composition of a secondary battery, thereby improving the electrode strength and the battery performance. It is not enough for the carbon nanotube dispersion to have a low viscosity (apparent) and good dispersibility. It is particularly effective to combine the complex elastic modulus, phase angle, viscosity and other previous indicators to judge the dispersion state.
[0130] The amount of the dispersant in the carbon nanotube dispersion of the present embodiment is preferably 10 to 100 parts by mass, more preferably 20 to 80 parts by mass, and even more preferably 20 to 50 parts by mass, based on 100 parts by mass of the carbon nanotubes.
[0131] The amount of the carbon nanotubes in the carbon nanotube dispersion of the present embodiment is preferably 0.2 to 20 parts by mass, more preferably 0.4 to 5 parts by mass, further preferably 0.4 to 2.5 parts by mass, and particularly preferably 0.5 to 2.0 parts by mass, relative to 100 parts by mass of the carbon nanotube dispersion.
[0132] The pH of the carbon nanotube dispersion of the present embodiment is preferably 6 to 12, more preferably 7 to 11, and particularly preferably 8 to 10.5. The pH of the carbon nanotube dispersion can be measured using a pH meter (pH meter F-52 manufactured by Horiba, Ltd.).
[0133] The carbon nanotube dispersion of the present embodiment preferably has a 50% particle size (D50) calculated by laser diffraction particle size distribution analysis of 1 μm to 20 μm, and more preferably 3 μm to 15 μm.
[0134] The viscosity of the carbon nanotube dispersion of the present embodiment is preferably less than 5000 mPa·s, more preferably less than 2000 mPa·s, as measured using a Brookfield viscometer at 60 rpm.
[0135] The carbon nanotube dispersion of the present embodiment is preferably a dispersion containing 0.4 parts by mass or more and 2.5 parts by mass or less of carbon nanotubes per 100 parts by mass of the carbon nanotube dispersion, and when the viscosity of the carbon nanotube dispersion is measured using a B-type viscometer at 6 rpm as α and the viscosity measured at 60 rpm as β, α / β is preferably 2.0≦α / β≦6.0.
[0136] In order to obtain the carbon nanotube dispersion of the present embodiment, it is preferable to perform a process of dispersing the carbon nanotubes in a solvent. The dispersing device used for the process is not particularly limited.
[0137] As the dispersing device, a dispersing machine commonly used in pigment dispersion, etc. can be used. For example, dispersing machines, homomixers, planetary mixers and other mixers, homogenizers (Advanced Digital Sonifer (registered trademark), Model (MODEL) 450DA manufactured by BRANSON, "Clearmix" manufactured by M-technique, "Filmix" manufactured by PRIMIX, "Abramix" manufactured by Silverson, etc.), paint conditioners (manufactured by Red Devil), colloid mills ("PUC colloid mill" manufactured by PUC, "Colloid mill MK" manufactured by IKA), cone mills ("Cone mill MKO" manufactured by IKA, etc.), ball mills, sand mills (SHINMARU The present invention also includes media dispersers such as "Dyno-mill" manufactured by ENTERPRISES, etc.), attritor, pearl mill ("DCP mill" manufactured by Eirich, etc.), co-ball mill, high pressure homogenizer ("Jenius PY" manufactured by Jenius, "Starburst" manufactured by SUGINO Machine, "nanomizer" manufactured by Nanomizer, etc.), media-free dispersers such as "Clear SS-5" manufactured by M-technique, "MICROS" manufactured by Nara Machinery, and other roll mills, but are not limited to these.
[0138] The carbon nanotube dispersion of the present embodiment is preferably prepared by applying shear stress to the conductive material composition to reduce the dispersed particle size to 250 μm or less and then dispersing the carbon nanotube dispersion at a pressure of 60 MPa to 150 MPa using a high-pressure homogenizer.
[0139] <Carbon nanotube resin composition>
[0140] The carbon nanotube resin composition as one embodiment of the present invention includes carbon nanotubes, a dispersant, a solvent, and a binder resin. In one embodiment, the carbon nanotube resin composition may include the carbon nanotube dispersion of the embodiment and a binder resin.
[0141] (Binder resin)
[0142] The so-called binder resin is a resin existing between substances such as carbon nanotubes.
[0143] As the binder resin of this embodiment, for example, there can be listed: polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylate, methacrylic acid, methacrylate, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, etc. as constituent units; polyurethane resin, polyester resin, phenol resin, epoxy resin, phenoxy resin, urea resin, melamine resin, alkyd resin, acrylic resin, formaldehyde resin, silicone resin, fluororesin; cellulose resin such as carboxymethyl cellulose; rubber such as styrene butadiene rubber and fluororubber; conductive resin such as polyaniline and polyacetylene, etc. In addition, it can also be a modified substance or mixture of these resins, and a copolymer. Among them, carboxymethyl cellulose, styrene butadiene rubber, and polyacrylic acid are preferred.
[0144] The carboxymethyl cellulose as a binder resin preferably has a high viscosity. For example, the viscosity of a 1% aqueous solution is preferably 500 mPa·s to 6000 mPa·s, and more preferably 1000 mPa·s to 3000 mPa·s. The viscosity of a 1% aqueous solution of carboxymethyl cellulose can be measured at 25° C. using a B-type viscometer rotor at a rotation speed of 60 rpm.
[0145] The carboxymethyl cellulose as the binder resin preferably has a high degree of etherification. For example, the degree of etherification is preferably 0.6 to 1.5, and more preferably 0.8 to 1.2.
[0146] The type or amount of the binder resin can be appropriately selected according to the properties of the coexisting substances such as carbon nanotubes and active materials. For example, regarding the amount of carboxymethyl cellulose used, when the mass of the graphite-based negative electrode active material and the silicon-based negative electrode active material is set to 100 mass%, the proportion of carboxymethyl cellulose is preferably 0.5 mass% to 3.0 mass%, and more preferably 1.0 mass% to 2.0 mass%.
[0147] If the styrene butadiene rubber is an oil-in-water emulsion, a material generally used as a binder for a graphite-based negative electrode can be used. Regarding the amount of styrene butadiene rubber used, when the mass of the graphite-based negative electrode active material and the silicon-based negative electrode active material is set to 100 mass %, the proportion of the styrene butadiene rubber is preferably 0.5 mass % to 3.0 mass %, and more preferably 1.0 mass % to 2.0 mass %.
[0148] Regarding the amount of polyacrylic acid used, when the mass of the graphite-based negative electrode active material and the silicon-based negative electrode active material is 100 mass %, the ratio of polyacrylic acid is preferably 1 to 25 mass %, more preferably 5 to 20 mass %.
[0149] In order to obtain the carbon nanotube resin composition of the present embodiment, it is preferred to mix and homogenize the carbon nanotube dispersion and the binder resin. Various known methods can be used as a mixing method. The carbon nanotube resin composition can be prepared using the dispersion device described in the carbon nanotube dispersion.
[0150] <Composite material slurry>
[0151] A composite material slurry as one embodiment of the present invention includes carbon nanotubes, a dispersant, an aqueous liquid medium, a binder resin, and an active material.
[0152] The carbon nanotubes include at least the carbon nanotubes of the above-described embodiment. The dispersant, the aqueous liquid medium, and the binder resin are as described above.
[0153] <Active substances>
[0154] The active material of this embodiment is a material that serves as a basis for the battery reaction. In terms of electromotive force, the active material is divided into a positive electrode active material and a negative electrode active material.
[0155] The positive electrode active material is not particularly limited, and metal compounds such as metal oxides and metal sulfides, and conductive polymers that can be doped or absorbed with lithium ions can be used.
[0156] For example, inorganic compounds such as oxides of transition metals such as Fe, Co, Ni, and Mn, composite oxides with lithium, and transition metal sulfides can be cited. Specifically, inorganic compounds such as MnO, V2O5, V6O 13 , transition metal oxide powders such as TiO2, composite oxide powders of lithium and transition metals such as lithium nickelate, lithium cobaltate, lithium manganate, lithium manganate with a spinel structure, lithium iron phosphate-based materials as phosphate compounds with an olivine structure, transition metal sulfide powders such as TiS2 and FeS, etc. In addition, conductive polymers such as polyaniline, polyacetylene, polypyrrole, and polythiophene can also be used. In addition, the inorganic compounds or organic compounds can also be mixed and used.
[0157] The negative electrode active material is not particularly limited as long as it can be doped or embedded with lithium ions. For example, metal Li, alloys thereof such as tin alloys, silicon alloys, and lead alloys, Li x Fe2O3、Li x Fe3O4、Li xWO2 (x is a number where 0<x<1), metal oxides such as lithium titanate, lithium vanadate, lithium silicate, conductive polymers such as polyacetylene, polyphenylene, amorphous carbonaceous materials such as soft carbon or hard carbon, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, carbon black, mesophase carbon black, resin-fired carbon materials, vapor-grown carbon fibers, carbon fibers, and other carbonaceous materials. These negative electrode active materials may also be used alone or in combination.
[0158] In one embodiment, as the negative electrode active material, it is preferable to use a graphite-based negative electrode active material in addition to the above-mentioned silicon-based negative electrode active material.
[0159] As silicon-based negative electrode active materials, for example, there can be listed: so-called metallurgical grade silicon produced by reducing silicon dioxide with carbon; or industrial grade silicon in which impurities are reduced by acid treatment or unidirectional solidification of metallurgical grade silicon; and high-purity silicon in different crystalline states such as single crystal, polycrystalline, and amorphous, produced by reacting silicon with silane; or silicon in which the crystalline state or precipitation state is adjusted while industrial grade silicon is made high-purity by sputtering or electron beam evaporation (EB (electron beam) evaporation) method.
[0160] In addition, silicon oxide, which is a compound of silicon and oxygen, or silicon and various alloys, and silicon compounds whose crystal states are adjusted by a quenching method, etc., can also be cited. Among them, a silicon-based negative electrode active material having a structure in which silicon nanoparticles are dispersed in silicon oxide and the outside is coated with a carbon film is preferred.
[0161] When the graphite-based negative electrode active material is 100% by mass, the amount of the silicon-based negative electrode active material is preferably 3% by mass to 50% by mass, and more preferably 5% by mass to 25% by mass.
[0162] The BET specific surface area of the active material of this embodiment is preferably 0.1 m 2 / g~10m 2 / g, more preferably 0.2m 2 / g~5m 2 / g, and more preferably 0.3m 2 / g~3m 2 / g.
[0163] The average particle size of the active material of this embodiment is preferably in the range of 0.5 μm to 50 μm, more preferably 2 μm to 20 μm. The average particle size of the active material referred to in this specification is the average value of the particle size measured by an electron microscope.
[0164] (Method for producing composite material slurry)
[0165] The composite material slurry of the present embodiment can be prepared by various conventionally known methods, such as a method of adding an active material to a carbon nanotube resin composition or a method of adding an active material to a carbon nanotube dispersion and then adding a binder resin.
[0166] In order to obtain the composite material slurry of this embodiment, it is preferred to perform a process of adding an active material to the carbon nanotube resin composition and dispersing it. The dispersing device used for the above process is not particularly limited. The composite material slurry can be obtained using the dispersing device described in the above carbon nanotube dispersion.
[0167] The amount of the active material in the composite material slurry of the present embodiment is preferably 20 to 80 parts by mass, more preferably 30 to 70 parts by mass, and still more preferably 40 to 60 parts by mass, based on 100 parts by mass of the composite material slurry.
[0168] The amount of the carbon nanotubes in the composite material slurry of the present embodiment is preferably 0.05 to 5 parts by mass, more preferably 0.05 to 1 part by mass, and still more preferably 0.1 to 0.5 parts by mass, relative to 100 parts by mass of the active material.
[0169] The amount of the binder resin in the composite material slurry of the present embodiment is preferably 0.5 to 30% by mass, more preferably 1 to 25% by mass, and particularly preferably 2 to 20% by mass, based on 100 parts by mass of the active material.
[0170] The amount of solid content in the composite material slurry of the present embodiment is preferably 30 to 90% by mass, more preferably 30 to 80% by mass, and still more preferably 40 to 70% by mass, relative to 100% by mass of the composite material slurry.
[0171] <Electrode film>
[0172] The electrode film as one embodiment of the present invention is formed by forming a composite material slurry into a film shape. For example, it is a coating film formed by applying the composite material slurry on a current collector and drying it to form an electrode composite material layer.
[0173] The material and shape of the current collector used in the electrode film of the present embodiment are not particularly limited, and the material and shape suitable for various secondary batteries can be appropriately selected. For example, as the material of the current collector, metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel can be listed. In addition, as the shape, a flat foil can generally be used, but a current collector with a roughened surface, a perforated foil-shaped current collector, and a mesh-shaped current collector can also be used.
[0174] As a method for applying the composite material slurry on the collector, there is no particular limitation, and known methods can be used. Specifically, die coating, dip coating, roll coating, blade coating, spray coating, gravure coating, screen printing or electrostatic coating can be listed. As a drying method, placement drying, air supply dryer, warm air dryer, infrared heater, far infrared heater, etc. can be used. However, it is not particularly limited to these.
[0175] In addition, after coating, a calendering treatment using a plate pressing machine, a calender roll, etc. may be performed. The thickness of the electrode composite material layer is generally 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.
[0176] <Non-aqueous electrolyte secondary battery>
[0177] The nonaqueous electrolyte secondary battery of this embodiment includes a positive electrode, a negative electrode, and an electrolyte.
[0178] As the positive electrode, a composite material slurry containing a positive electrode active material is applied to a current collector and then dried to form an electrode film.
[0179] As the negative electrode, a composite material slurry containing a negative electrode active material is applied to a current collector and then dried to form an electrode film.
[0180] As an electrolyte, various previously known electrolytes in which ions can move can be used. For example, LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is phenyl) etc. include electrolytes containing lithium salts, but are not limited to these, and electrolytes containing sodium salts can also be used. The electrolyte is preferably used as an electrolyte after being dissolved in a non-aqueous solvent.
[0181] The non-aqueous solvent is not particularly limited, and examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octalactone; glyme such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and cyclopentane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.
[0182] The non-aqueous electrolyte secondary battery of the present embodiment preferably includes a separator. Examples of the separator include polyethylene non-woven fabric, polypropylene non-woven fabric, polyamide non-woven fabric, and non-woven fabrics subjected to hydrophilic treatment, but are not particularly limited to these.
[0183] The structure of the nonaqueous electrolyte secondary battery of this embodiment is not particularly limited, and generally includes a positive electrode and a negative electrode, and a separator provided as required, and can be made into various shapes corresponding to the purpose of use, such as paper type, cylindrical type, button type, and stacked type.
[0184] The nonaqueous secondary electrolyte secondary battery of the above-described embodiment can be preferably used in various application fields. For example, it can be preferably used as a nonaqueous secondary electrolyte secondary battery mounted on a vehicle.
[0185] Example
[0186] The present invention is described in more detail below with reference to the following examples. The present invention is not limited to the following examples unless it exceeds the gist of the present invention. In the examples, "carbon nanotube" is sometimes referred to as "CNT". In addition, "part" means "part by mass" and "%" means "% by mass" unless otherwise specified.
[0187] <Measurement methods of physical properties>
[0188] The physical properties of CNTs used in each of the examples and comparative examples described below were measured by the following methods.
[0189] <pH of CNT aqueous dispersion>
[0190] 2 g of CNT was weighed in a 450 mL SM sample bottle (manufactured by Sansho Co., Ltd.), 200 mL of ion exchange water was added, and an ultrasonic homogenizer (Advanced Digital Sonifer (registered trademark), model (MODEL) 450DA, manufactured by BRANSON) was used to disperse the mixture for 1 minute under ice bath cooling with an amplitude of 50%. Thereafter, the filtrate was recovered through a nylon mesh with a pore size of 48 μm. Further thereafter, the filtrate was allowed to stand in a thermostatic bath at 25° C. for more than 1 hour, and then measured using a pH meter (manufactured by Horiba, Ltd., pH meter (pH METER) F-52). The result is used as the pH of the CNT aqueous dispersion.
[0191] <BET specific surface area of CNT>
[0192] 0.03 g of CNT was weighed using an electronic balance (Sartorius, MSA225S100DI) and then dried at 110° C. for 15 minutes while degassing. The BET specific surface area of CNT was then measured using a fully automatic specific surface area measuring device (Mountech, HM-model 1208).
[0193] <Average fiber length of CNT>
[0194] Using an electronic balance (MSA225S100DI manufactured by Sartorius), 0.2 g of CNT was weighed in a 450 mL SM sample bottle (manufactured by Sansho Co., Ltd.), 200 mL of toluene was added, and an ultrasonic homogenizer (Advanced Digital Sonifer (registered trademark), model (MODEL) 450DA, manufactured by Branson) was used to disperse the mixture at an amplitude of 50% for 1 minute to prepare a CNT dispersion.
[0195] After that, after dropping a few μL of CNT dispersion on the mica substrate, it was dried in an electric oven at 120°C to make a substrate for observing the CNT fiber length of the powder. Thereafter, platinum was used to sputter the surface of the substrate made for observing the CNT fiber length of the powder. Then, a scanning electron microscope (SEM) was used for observation. During the observation, in conjunction with the fiber length of the CNT, a plurality of photographs containing more than 10 CNTs in the field of view were taken at a magnification of 5000 times or 20,000 times, and the fiber length of 100 CNTs extracted at random was measured, and the average value was taken as the average fiber length (μm) of the CNT.
[0196] <G / D ratio of CNT>
[0197] CNT was set in a Raman microscope (XploRA, manufactured by Horiba, Ltd.) and measured using a laser wavelength of 532 nm. The measurement conditions were as follows: acquisition time 60 seconds, accumulation times 2 times, ND filter 10%, objective lens magnification 20 times, confocal aperture 500, slit width 100 μm, measurement wavelength 100 cm -1 ~3000cm -1 The CNTs for measurement were separated and taken out onto a glass slide and flattened using a spatula. Among the peaks obtained, the peak at 1560 cm -1 ~1600cm -1 The maximum peak intensity is set to G in the range of 1310 cm -1 ~1350cm -1 The maximum peak intensity in the range of is set as D, and the ratio of G / D is set as the G / D ratio of CNT.
[0198] <Average outer diameter of CNT>
[0199] Using an electronic balance (manufactured by Sartorius, MSA225S100DI), 0.2 g of CNT was weighed in a 450 mL SM sample bottle (manufactured by Sansho Co., Ltd.), 200 mL of toluene was added, and an ultrasonic homogenizer (Advanced Digital Sonifer (registered trademark), model (MODEL) 450DA, manufactured by BRANSON) was used to disperse the CNTs for 5 minutes under ice bath cooling with an amplitude of 50%. Thereafter, the CNT dispersion was appropriately diluted, and a few μL was added dropwise in the form of a collodion film. After drying at room temperature, it was directly observed using a transmission electron microscope (H-7650, manufactured by Hitachi, Ltd.). The observation was performed at a magnification of 50,000 times, and multiple photos containing more than 10 CNTs in the field of view were taken, and the outer diameters of 300 CNTs randomly extracted from the photos were measured, and the average value was taken as the average outer diameter (nm) of the CNTs.
[0200] <Volume resistivity of CNT>
[0201] Using a powder resistivity measuring device (Mitsubishi Chemical Analytech Co., Ltd.: Loresta GP Powder Resistivity Measuring System MCP-PD-51), the sample mass was set to 1.2 g, and a powder probe unit (four-probe-ring electrode, electrode spacing 5.0 mm, electrode radius 1.0 mm, sample radius 12.5 mm) was used. The applied voltage limiter was set to 90 V to measure the volume resistivity [Ω·cm] of the conductive powder under various pressures. For 1 g / cm 3 The volume resistivity value of CNT at a density of 1.5 Å was evaluated.
[0202] <Carbon purity of CNT>
[0203] CNTs were acid-decomposed using a microwave sample pretreatment device (Milestone General, ETHOS1) to extract the metals contained in the CNTs. Afterwards, the metal content in the extract was calculated using a polytype inductively coupled plasma (ICP) emission spectrometer (Agilent, 720-ES). The carbon purity of CNTs was calculated as follows.
[0204] (Formula 4)
[0205] Carbon purity (%) = ((CNT mass - metal mass in CNT) ÷ CNT mass) × 100%
[0206] <Initial viscosity of CNT dispersion>
[0207] After the CNT dispersion is allowed to stand in a thermostatic bath at 25°C for more than 1 hour, the CNT dispersion is fully stirred and then immediately measured using a B-type viscometer rotor at a rotation speed of 60 rpm. Regarding the rotor used in the measurement, No. 1 is used when the viscosity value is less than 100 mPa·s, No. 2 is used when it is greater than 100 mPa·s and less than 500 mPa·s, No. 3 is used when it is greater than 500 mPa·s and less than 2000 mPa·s, and No. 4 is used when it is greater than 2000 mPa·s and less than 10000 mPa·s. The evaluation criteria for the initial viscosity are as follows.
[0208] (Evaluation Criteria)
[0209] 4 (excellent): less than 500 mPa·s
[0210] 3 (good): 500 mPa·s or more and less than 2000 mPa·s
[0211] 2 (allowable): 2000 mPa·s or more and 5000 mPa·s or less
[0212] 1 (Not allowed): More than 5000mPa·s
[0213] <Stability of CNT dispersion>
[0214] After the CNT dispersion was allowed to stand in a thermostatic chamber at 25° C. for 1 week, the CNT dispersion was sufficiently stirred and then immediately measured using a B-type viscometer rotor at a rotation speed of 60 rpm. The evaluation criteria for stability are as follows.
[0215] (Evaluation Criteria)
[0216] 4 (excellent): The viscosity is the same as the initial viscosity.
[0217] 3 (good): The viscosity changes slightly.
[0218] 2 (OK): Viscosity increased but no gelation.
[0219] 1 (Not acceptable): Gelation.
[0220] <Thixotropy of CNT dispersion (α / β)>
[0221] After the CNT dispersion was allowed to stand in a thermostatic bath at 25°C for 24 hours, the CNT dispersion was fully stirred and then immediately measured using a B-type viscometer rotor at a rotation speed of 6 rpm. Thereafter, the B-type viscometer rotor was immediately measured at a rotation speed of 60 rpm. At this time, the value of α / β when the viscosity measured at 6 rpm was set as α and the viscosity measured at 60 rpm was set as β was evaluated according to the following criteria.
[0222] (Evaluation Criteria)
[0223] 4 (Excellent): 2 or more but less than 4
[0224] 3 (Good): 4 or higher but less than 5
[0225] 2 (OK): 5 or more and 6 or less
[0226] 1 (Not allowed): less than 2 or more than 6
[0227] <Complex elastic modulus and phase angle of CNT dispersion>
[0228] The complex elastic modulus and phase angle of the CNT dispersion were evaluated in the following manner: using a rheometer (RheoStress 1 rotational rheometer manufactured by Thermo Fisher Scientific, Inc.) with a cone of 35 mm in diameter and 2°, dynamic viscoelasticity measurements were performed at 25°C and a frequency of 1 Hz with a strain rate ranging from 0.01% to 5%.
[0229] The evaluation criteria of the complex elastic modulus are as follows.
[0230] (Evaluation Criteria)
[0231] 3 (excellent): 5Pa or more and less than 50Pa
[0232] 2 (good): 1Pa or more and less than 5Pa, or 50Pa or more and less than 100Pa
[0233] 1 (Not acceptable): Less than 1Pa or more than 100Pa
[0234] Furthermore, the product (X×Y) of the obtained complex elastic modulus X (Pa) and the phase angle Y (°) was calculated. The product (X×Y) of the complex elastic modulus X (Pa) and the phase angle Y (°) was evaluated according to the following evaluation criteria.
[0235] (Evaluation Criteria)
[0236] 2 (Good): 100 or more and 1500 or less
[0237] 1 (Not allowed): less than 100 or more than 1500
[0238] <50% particle size of CNT dispersion (D50)>
[0239] The 50% particle size was measured using a particle size distribution measuring device (Partica LA-960V2, manufactured by HORIBA). The circulation / ultrasonic operation conditions were set to circulation speed: 3, ultrasonic intensity: 7, ultrasonic time: 1 minute, stirring speed: 1, stirring mode: continuous. In addition, ultrasonic operation was performed in the exhaust gas with an ultrasonic intensity of 7 and an ultrasonic time of 5 seconds. The refractive index of water was set to 1.333, and the refractive index of the carbon material was set to 1.92. The measurement was performed after diluting the measurement sample so that the transmittance of the red laser diode became 60% to 80%, and the basis of the particle size was set to volume. For the 50% particle size, evaluation was performed according to the following evaluation criteria.
[0240] (Evaluation Criteria)
[0241] 3 (excellent): 3 μm or more and 15 μm or less
[0242] 2 (good): 1 μm or more and less than 3 μm or more than 15 μm and less than 20 μm
[0243] 1 (Not acceptable): less than 1 μm or more than 20 μm
[0244] <Measurement of pH of CNT dispersion>
[0245] After the CNT dispersion was left to stand in a thermostatic chamber at 25° C. for 1 hour or longer, the CNT dispersion was sufficiently stirred and then measured using a pH meter (pH meter F-52 manufactured by Horiba, Ltd.).
[0246] <Volume resistivity of electrode film>
[0247] Use the applicator to apply the electrode at a weight per unit area of 8 mg / cm 2 After the composite material slurry is applied to the copper foil, the coating is dried in an electric oven at 120°C ± 5°C for 25 minutes. Thereafter, Mitsubishi Chemical Analytech (Mitsubishi Chemical Analytech) (stock) is used to manufacture: Loresta GP, MCP-T610 to measure the surface resistivity (Ω / Υ) of the dried coating. After the measurement, multiply the thickness of the electrode composite material layer formed on the copper foil as the volume resistivity (Ω·cm) of the electrode film for the negative electrode. The thickness of the electrode composite material layer is measured using a film thickness meter (manufactured by NIKON, DIGIMICRO MH-15M), and the average value obtained from measuring 3 points in the electrode film is subtracted from the thickness of the copper foil to obtain the volume resistivity (Ω·cm) of the electrode film.
[0248] <Peel strength of electrode film>
[0249] Use the applicator to apply the electrode at a weight per unit area of 8 mg / cm 2 After the composite material slurry is applied to the copper foil in an electric oven, the coating is dried for 25 minutes at 120°C ± 5°C. Thereafter, the coating direction is used as the major axis and cut into two 90mm×20mm rectangles. In the determination of peel strength, a desktop tensile tester (manufactured by Toyo Seiki Seisakusho, Strograph E3) is used, and the 180-degree peel test method is used for evaluation. Specifically, a 100mm×30mm double-sided tape (No.5000NS, manufactured by Nitoms) is attached to a stainless steel plate, so that the prepared battery electrode composite material layer is closely attached to the other side of the double-sided tape, and it is peeled off while being stretched from bottom to top at a certain speed (50mm / minute), and the average value of the stress at this time is used as the peel strength.
[0250] <Production of standard positive electrode>
[0251] The standard positive electrode used in the examples and comparative examples described below was produced by the following method.
[0252] First, 93 parts by mass of a positive electrode active material (manufactured by BASF TODA Battery Materials, HED (registered trademark) NCM-111 1100), 4 parts by mass of acetylene black (manufactured by DENKA Co., Ltd., DENKA BLACK (registered trademark) HS100), and 3 parts by mass of polyvinylidene fluoride (PVDF) (manufactured by Kureha Battery Material Japan Co., Ltd., Kureha KF polymer W#1300) were added to a 150 cm 3 After adding 20.5 parts by mass of NMP into a plastic container, use a spatula to mix until the powder is uniform. Thereafter, 20.5 parts by mass of NMP are added, and a self-rotating orbital mixer (Are-310 manufactured by Thinky) is used to stir at 2000 rpm for 30 seconds. Thereafter, a spatula is used to mix the mixture in the plastic container until it is uniform, and the self-rotating orbital mixer is used to stir at 2000 rpm for 30 seconds. Furthermore, 14.6 parts by mass of NMP are added, and the self-rotating orbital mixer is used to stir at 2000 rpm for 30 seconds. Finally, a high-speed stirrer is used to stir at 3000 rpm for 10 minutes to obtain a composite material slurry for the positive electrode. Thereafter, the composite material slurry for the positive electrode is applied to an aluminum foil with a thickness of 20 μm as a current collector using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes, and the unit area weight per unit area of the electrode is adjusted to 20 mg / cm 2 The composite material layer was then rolled using a roller press (manufactured by Thank-Metal Co., Ltd., 3 t hydraulic roller press) to obtain a density of 3.1 g / cm 3 The standard positive electrode.
[0253] (Production of standard negative electrode)
[0254] In a 150 ml plastic container, 0.5 parts by mass of acetylene black (DENKA BLACK (registered trademark) HS-100, manufactured by DENKA), 1 part by mass of MAC500LC (sodium carboxymethylcellulose Sunrose special type MAC500L, manufactured by Nippon Paper Industries, non-volatile content 100%), and 98.4 parts by mass of water were added, and stirred at 2000 rpm for 30 seconds using an auto-rotational mixer (Degassing Rentaro, ARE-310 manufactured by Thinky). Furthermore, 87 parts by mass of artificial graphite (CGB-20, manufactured by Nippon Graphite Industries) and 10 parts by mass of silicon as an active material were added, and stirred at 3000 rpm for 10 minutes using a high-speed stirrer. Then, 3.1 parts by mass of SBR (TRD2001, manufactured by JSR Corporation) was added and stirred at 2000 rpm for 30 seconds using the above-mentioned rotary mixer to obtain a composite material slurry for the negative electrode. Thereafter, a coating device was used to coat the electrode with a unit area weight of 8 mg / cm 2 The negative electrode composite material slurry was applied to the copper foil, and the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes. Then, a roller press (manufactured by Thank-Metal Co., Ltd., 3t hydraulic roller press) was used for calendering to produce a composite material layer with a density of 1.7 g / cm 3 The standard negative electrode.
[0255] <Evaluation of rate characteristics of lithium-ion secondary batteries>
[0256] The laminated lithium-ion secondary battery was placed in a constant temperature room at 25°C, and a charge and discharge device (manufactured by Hokuto Electric Co., Ltd., SM-8) was used for charge and discharge measurement. After constant current and constant voltage charging (cut-off current 1.1mA (0.02C)) at a charge end voltage of 4.2V at a charging current of 11mA (0.2C), constant current discharge was performed at a discharge current of 11mA (0.2C) with a discharge end voltage of 2.5V. After repeating the above operation three times, constant current and constant voltage charging (cut-off current 1.1mA (0.02C)) was performed at a charge end voltage of 4.2V at a charging current of 11mA (0.2C), and constant current discharge was performed at a discharge current of 0.2C and a discharge current of 3C until the discharge end voltage reached 2.5V, and the discharge capacity was calculated respectively. The rate characteristic is the ratio of the 0.2C discharge capacity to the 3C discharge capacity, which can be expressed by the following (Formula 5).
[0257] (Formula 5)
[0258] Rate characteristics = 3C discharge capacity / third 0.2C discharge capacity × 100 (%)
[0259] <Evaluation of cycle characteristics of lithium-ion secondary batteries>
[0260] The laminated lithium-ion secondary battery was placed in a constant temperature room at 25°C, and a charge and discharge device (manufactured by Hokuto Electric Co., Ltd., SM-8) was used for charge and discharge measurements. After constant current and constant voltage charging (cut-off current 1.38mA (0.025C)) at a charge current of 55mA (1C) and a charge termination voltage of 4.2V, constant current discharge was performed at a discharge current of 55mA (1C) and a discharge termination voltage of 2.5V. The above operation was repeated 200 times. 1C is set as the current value that discharges the theoretical capacity of the positive electrode in 1 hour. The cycle characteristics are the ratio of the 1C discharge capacity of the third time at 25°C to the 1C discharge capacity of the 200th time, which can be expressed by the following (Formula 6).
[0261] (Formula 6)
[0262] Cycle characteristics = 1C discharge capacity at the third time / 1C discharge capacity at the 200th time × 100 (%)
[0263] <Synthesis of copolymer of acrylonitrile and acrylic acid>
[0264] 100 parts of acetonitrile were placed in a reaction vessel including a gas inlet pipe, a thermometer, a condenser, and a stirrer, and replaced with nitrogen. The reaction vessel was heated to 75°C, and a mixture of 90.0 parts of acrylonitrile, 10.0 parts of acrylic acid, and 5.0 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by NOF Corporation; V-65) was added dropwise over 3 hours to carry out a polymerization reaction. After the addition was completed, the reaction was continued at 75°C for 1 hour, and then 0.5 parts of perbutyl O was added, and the reaction was continued at 75°C for 1 hour. Thereafter, the conversion rate was confirmed to exceed 98% by non-volatile component determination, and the dispersion medium was completely removed by vacuum concentration to obtain a copolymer of acrylonitrile and acrylic acid. The weight average molecular weight (Mw) of the copolymer of acrylonitrile and acrylic acid is 45,000.
[0265] <Dispersant>
[0266] Carboxymethylcellulose (manufactured by Nippon Paper Industries, Ltd., Sunrose A APP-84, weight average molecular weight 17,600) hereinafter referred to as CMC (carboxymethylcellulose).
[0267] Carboxymethyl cellulose (manufactured by Nippon Paper Industries, Ltd., Sunrose (registered trademark) F01MC, weight average molecular weight 55,600) hereinafter referred to as CMC2.
[0268] Carboxymethyl cellulose (manufactured by Nippon Paper Industries, Ltd., Sunrose (registered trademark) F05MC, weight average molecular weight 104,500) Hereinafter, abbreviated as CMC3.
[0269] Polyvinyl pyrrolidone (manufactured by Nippon Shokubai Co., Ltd., K-30, weight average molecular weight 40,000), hereinafter referred to as PVP.
[0270] ·Copolymer of acrylonitrile and acrylic acid. Hereinafter referred to as PAN.
[0271] <Additives>
[0272] 2-aminoethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., Wako Grade 1)
[0273] ·Na2CO3 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., Wako Grade 1)
[0274] ·NaOH (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., Wako Grade 1)
[0275] <Defoaming agent>
[0276] Surfynol 104E (manufactured by Nissin Chemical Industry Co., Ltd., HLB value 4, surface tension 33mN / m)
[0277] Surfynol 440 (manufactured by Nissin Chemical Industry Co., Ltd., HLB value 8, surface tension 32 mN / m)
[0278] SN defoamer 777 (manufactured by Sannopco)
[0279] <Synthesis of cobalt hydroxide>
[0280] Cobalt hydroxide in which plate-like primary particles formed spherical secondary particles was produced by the method described in paragraph
[0091] of Japanese Patent Application Laid-Open No. 2012-072050. The residual sulfur content in the produced cobalt hydroxide was confirmed by ICP analysis to be 1500 ppm.
[0281] <Synthesis of CNT synthesis catalyst>
[0282] Instead of 30 parts of cobalt hydroxide (II), 30 parts of cobalt hydroxide in which the plate-like primary particles are formed into spherical secondary particles is used, and in addition, the CNT synthesis catalyst (X) is prepared using the method described in paragraphs
[0147] and
[0148] of Japanese Patent Gazette No. 2019-108256.
[0283] Instead of 30 parts of cobalt hydroxide (II), 30 parts of cobalt hydroxide in which the plate-like primary particles are formed into spherical secondary particles is used, and in addition, the CNT synthesis catalyst (Y) is prepared using the method described in paragraph
[0117] of Japanese Patent Gazette No. 2018-150218.
[0284] A CNT synthesis catalyst (Z) was obtained by the same method as in the CNT synthesis catalyst (X), except that 60 parts of cobalt acetate tetrahydrate was used instead of 30 parts of cobalt (II) hydroxide.
[0285] (Example 1-1)
[0286] <Synthesis of CNT(A)>
[0287] In the central part of a horizontal reaction tube with an internal volume of 10L that can be pressurized and heated by an external heater, a quartz glass heat-resistant dish with 1g of the CNT synthesis catalyst (X) is arranged. While injecting nitrogen, exhaust is performed, the air in the reaction tube is replaced by nitrogen, and the ambient temperature in the horizontal reaction tube is heated to 700°C. After reaching 700°C, propane gas as a hydrocarbon is introduced into the reaction tube at a flow rate of 2L per minute, and the reaction is contacted for 60 minutes. After the reaction is completed, the gas in the reaction tube is replaced by nitrogen, the temperature of the reaction tube is cooled to below 100°C and taken out, thereby obtaining CNT (A).
[0288] (Example 1-2 to Example 1-12, Example 1-15 to Example 1-17)
[0289] <Synthesis of CNT(B) to CNT(S)>
[0290] CNT (B) to CNT (S) were produced by the same method as in Example 1 except that the CNT synthesis catalyst, reaction temperature, carbon source, and gas flow rate were changed to those shown in Table 1.
[0291] [Table 1]
[0292] Table 1
[0293]
[0294] (Examples 1-13)
[0295] <Synthesis of CNT(GA)>
[0296] 10 kg of CNT (G) was weighed into a 120 L heat-resistant container, and the heat-resistant container containing CNT was placed in a furnace. Thereafter, nitrogen was introduced into the furnace, and the air in the furnace was exhausted while maintaining a positive pressure. After the oxygen concentration in the furnace reached 0.1% or less, it was heated to 1600°C for 30 hours. While maintaining the temperature in the furnace at 1600°C, chlorine was introduced at a rate of 50 L / min for 50 hours. Thereafter, nitrogen was introduced at 50 L / min, and cooled while maintaining a positive pressure to obtain CNT (GA).
[0297] (Examples 1-14)
[0298] CNT (IA) was obtained by the same method as in Example 1-13 except that CNT (I) was used instead of CNT (G).
[0299] (Comparative Example 1-1)
[0300] Weigh 10g of CNT (G) into a 1L glass container, add 500g of 20% hydrochloric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and stir thoroughly with a stirrer. Thereafter, dilute thoroughly with ion exchange water and filter under reduced pressure using a membrane filter. After repeating the dilution and filtration operations, move the CNT to a bucket made of polytetrafluoroethylene (PTFE) and dry it in an oven at 80°C to obtain CNT (GB). The pH of CNT (GB) is 4.0.
[0301] (Comparative Example 1-2 to Comparative Example 1-4)
[0302] Multilayer carbon nanotubes (manufactured by Nanocyl, NC7000) were used as CNT (M), carbon nanotubes (manufactured by Showa Denko, VGCF-H) were used as CNT (N), and multilayer carbon nanotubes (manufactured by TPR, millimeter-scale CNT) were used as CNT (O). Single-layer carbon nanotubes (manufactured by OCSiAl, TUBALL) were used as CNT (P).
[0303] Table 2 shows the results of evaluating the CNTs of Examples 1-1 to 1-17, Comparative Examples 1-1 to 1-4, and Reference Example 1-1.
[0304]
[0305] The pH of the aqueous dispersions of CNTs in Examples 1-1 to 1-17 were all within the range of 8.0 to 10.0, and the BET specific surface areas were all 200 m 2 / g~800m 2Furthermore, the average fiber length (Y) and the BET specific surface area (X) of CNTs satisfy the following relationship.
[0306] Y=-aX+b
[0307] (a and b are constants, 2.2≦a≦3.5, 2300≦b≦5000)
[0308] More specifically, for example, regarding the CNT (E) of Example 1-5, the average fiber length (Y) is 1800 nm, the BET specific surface area (X) is 330 m 2 / g, and when a is set to 2.7, b = aX + Y = 2.7 × 330 + 1800 = 2691. In addition, regarding the CNT (K) of Example 1-11, when the average fiber length (Y) is 4000 nm and the BET specific surface area (X) is 360 m 2 / g, when a is set to 2.7, b=aX+Y=2.7×360+4000=4972.
[0309] Figure 1 This is a graph showing the relationship between the BET specific surface area and the average fiber length of the CNTs produced in the examples of the present invention and the carbon nanotubes (CNTs) used in the comparative examples and reference examples. Figure 1 It is understood that in CNT (A) to CNT (F) of Examples 1-1 to 1-6, X and Y are related to the following relationship (regression line).
[0310] Y=-2.2X+2,678.7
[0311] In the CNTs (G) to (L) of Examples 1-7 to 1-12, X and Y are related to the following relationship (regression line).
[0312] Y=-3.5X+4,791.4
[0313] In the CNT (GA) and CNT (IA) of Examples 1-13 and 1-14, X and Y are related to the following relationship (regression line).
[0314] Y=-1.2X+2,600.0
[0315] On the other hand, the pH of the aqueous dispersions of CNT (GB) of Comparative Example 1-1, CNT (N) of Comparative Example 1-3, CNT (O) of Comparative Example 4, and CNT (P) of Reference Example 1-1 were all outside the range of 8.0 to 10.0. In addition, the BET specific surface area of CNT (N) of Comparative Example 1-3 and CNT (P) of Reference Example 1-1 was 200 m 2 / g~800m 2 In addition, in the CNT (M) of Comparative Example 1-2 and the CNT (O) of Comparative Example 1-4, with respect to the values of the average fiber length (Y) and the BET specific surface area (X) of the CNT, the following formula
[0316] Y=-aX+b
[0317] The constants a and b that are equal on both sides do not exist in the range of 2.2≦a≦3.5, 2300≦b≦5000.
[0318] For example, regarding the "CNT (M)" of Comparative Example 1-2, when the average fiber length is 1100 nm, the BET specific surface area X is 210, and 2.2≦a≦3.5, the range of 2300≦b≦5000 is not satisfied. Figure 1 This situation can also be clarified.
[0319] (Example 2-1)
[0320] According to the composition shown in Table 3, ion exchange water, dispersant, additives, and defoaming agent are added to a stainless steel container, and stirred until uniform by a disperser. Thereafter, CNT (A) is added while stirring with a disperser, and a square hole high shear screen is installed on a high shear mixer (L5M-A, manufactured by SILVERSON), and the whole is made uniform at a speed of 8,600 rpm, and a grinder is used for batch dispersion until the dispersed particle size reaches 250 μm or less. Then, the dispersed liquid is supplied from the stainless steel container via a pipe to a high pressure homogenizer (Star Burst Labo HJP-17007, manufactured by SUGINOMACHINE), and 20 passes are performed for dispersion treatment. The dispersion treatment is carried out using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 80 MPa.
[0321] (Example 2-2 to Comparative Example 2-4)
[0322] CNT (A) was replaced with CNT (B) to CNT (O), and CNT dispersions (B) to (N) were prepared with the compositions shown in Table 3. CNT dispersion (O) had a high viscosity and could not be dispersed using a high-pressure homogenizer.
[0323] (Example 2-31 to Example 2-32)
[0324] According to the composition shown in Table 3, NMP, dispersant and additives are added to a stainless steel container and stirred until uniform by a disperser. Thereafter, CNT (C) is added while stirring with a disperser, and a square hole high shear screen is installed on a high shear mixer (L5M-A, manufactured by SILVERSON), and the whole is made uniform at a speed of 8,600 rpm, and a grinder is used for batch dispersion until the dispersed particle size reaches 250 μm or less. Then, the dispersed liquid is supplied from the stainless steel container via a pipe to a high pressure homogenizer (Star Burst Labo HJP-17007, manufactured by SUGINO MACHINE), and 20 passes are performed for dispersion treatment. The dispersion treatment is carried out using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 80 MPa.
[0325]
[0326]
[0327] <Production of Carbon Nanotube Resin Composition and Composite Material Slurry>
[0328] (Example 3-1)
[0329] In the capacity of 150cm 3After adding CNT dispersion (CNT dispersion A), an aqueous solution containing 2 wt% CMC (manufactured by Daicel Finechem Co., Ltd., #1190) and water to a plastic container, agitation was performed at 2,000 rpm for 30 seconds using a rotation-revolution mixer (Defoaming Rentaro manufactured by Thinky, ARE-310) to obtain a carbon nanotube resin composition (A). Subsequently, silicon monoxide (manufactured by Osaka Titanium Technologies, SILICON MONOOXIDE, SiO1.3C 5μm) was added to the carbon nanotube resin composition, and the mixture was stirred at 2,000 rpm for 5 minutes using the rotation-revolution mixer, and then fully mixed using a spatula. Furthermore, graphite (manufactured by Nippon Graphite Industries, CGB-20) was added, and the mixture was stirred at 2,000 rpm for 5 minutes using the rotation-revolution mixer, and then fully mixed using a spatula. Finally, SBR (manufactured by JSR, styrene butadiene rubber TRD2001) was added, and the mixture was stirred at 2000 rpm for 30 seconds using the rotation and revolution mixer to obtain a composite material slurry (A). The non-volatile component of the negative electrode composite material composition was set to 48% by mass. Among the non-volatile components of the negative electrode composite material composition, the non-volatile component ratio of graphite: silicon monoxide: CNT: CMC (#1190): SBR was set to 87:10:0.5:1:1.5.
[0330] (Example 3-2 to Comparative Example 3-3)
[0331] Carbon nanotube resin compositions (B) to (N) and composite material slurries (B) to (N) were obtained in the same manner as in Example 3-1 except that the CNT dispersions described in Table 4 were used.
[0332] (Example 3-31)
[0333] In capacity 150cm 3 In a plastic container, 7.0 parts by mass of NMP in which 8% by mass of PVDF (polyvinylidene fluoride, manufactured by Solvay, Solef #5130) was dissolved was weighed. Then, 18.7 parts by mass of CNT dispersion (C4) was added, and the mixture was stirred at 2000 rpm for 30 seconds using a rotary mixer (Degassing Rentaro, ARE-310) to obtain a CNT resin composition (C4).
[0334] Then, 36.9 parts of positive electrode active material (manufactured by BASF TODA Battery Materials Co., Ltd., HED (registered trademark) NCM-111 1100) was added, and the mixture was stirred at 2000 rpm for 2.5 minutes using a rotation and revolution mixer (Degassing Rentaro, ARE-310) to obtain positive electrode composite material slurry (C4).
[0335] (Example 3-32)
[0336] A CNT resin composition (C5) and a positive electrode composite material slurry (C5) were obtained by the same method as in Example 3-31 except that the CNT dispersion (C5) was used.
[0337] [Table 4]
[0338] Table 4
[0339]
[0340] (Example 4-1)
[0341] After applying the composite material slurry (A) to a copper foil with a thickness of 20 μm using an applicator, the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes to prepare an electrode film for the negative electrode. Thereafter, the electrode film was rolled using a roller press (manufactured by Thank-Metal, 3t hydraulic roller press) to obtain a negative electrode (negative electrode A). In addition, the unit area weight of each unit of the composite material layer was 8 mg / cm 2 The density of the composite material layer after calendering is set to 1.6 g / cc.
[0342] (Example 4-2 to Comparative Example 4-3)
[0343] Composite material slurries (B) to (N) were used instead of composite material slurries (A) to produce negative electrode films (B) to (N) and negative electrodes (B) to (N).
[0344] (Example 4-31)
[0345] Use the applicator to apply the electrode at a weight per unit area of 20 mg / cm 2 After the composite material slurry (C4) was applied to the aluminum foil in a manner, the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes to obtain a positive electrode film (C4). Thereafter, the positive electrode film (C4) was rolled using a roller press (manufactured by Thank-Metal, 3t hydraulic roller press) to obtain a positive electrode (A). In addition, the unit area weight of each unit of the composite material layer was 20 mg / cm2 The density of the composite material layer after calendering is set to 3.1 g / cc.
[0346] (Example 4-32)
[0347] A positive electrode film (C5) and a positive electrode (C5) were produced by the same method as in Example 4-31, except that the composite material slurry (C4) was changed to the composite material slurry (C5).
[0348] The evaluation results of the negative electrode films and the positive electrode films produced in Example 4-1 to Comparative Example 4-3 are shown in Table 5. The criteria for each evaluation of the electrode films are as follows.
[0349] (Volume resistivity)
[0350] 3 (excellent): The volume resistivity (Ω·cm) of the electrode film is less than 0.15
[0351] 2 (good): The volume resistivity (Ω·cm) of the electrode film is 0.15 or more and less than 0.3
[0352] 1 (Not acceptable): The volume resistivity (Ω·cm) of the electrode film is 0.3 or more
[0353] (Tightness)
[0354] 3 (excellent): peel strength (N / cm) is 0.5 or more
[0355] 2 (good): Peel strength (N / cm) is 0.3 or more and less than 0.5
[0356] 1 (Not acceptable): Peel strength (N / cm) less than 0.3
[0357] The evaluation criteria of the positive electrode film are as follows.
[0358] (Volume resistivity)
[0359] 3 (good): The volume resistivity (Ω·cm) of the electrode film is less than 10
[0360] 2 (OK): The volume resistivity (Ω·cm) of the electrode film is 10 or more and less than 15
[0361] 1 (Not acceptable): The volume resistivity (Ω·cm) of the electrode film is 15 or more
[0362] (Tightness)
[0363] 3 (good): Peel strength (N / cm) is 0.3 or more
[0364] 2 (acceptable): Peel strength (N / cm) is 0.2 or more and less than 0.3
[0365] 1 (Not acceptable): Peel strength (N / cm) less than 0.2
[0366] [Table 5]
[0367] Table 5
[0368]
[0369]
[0370] (Example 5-1)
[0371] The negative electrode (A) and the standard positive electrode were punched into 50mm×45mm and 45mm×40mm, respectively, and the separator (porous polypropylene film) to be inserted therebetween was inserted into an aluminum laminate bag and dried in an electric oven at 60°C for 1 hour. Afterwards, 2 mL of an electrolyte solution (a mixed solvent was prepared by mixing ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a ratio of 3:5:2 (volume ratio), and as an additive, 1 part of vinyl carbonate (VC) and fluoroethylene carbonate (FEC) were added to 100 parts by mass of the mixed solvent, and LiPF6 was dissolved in a non-aqueous electrolyte solution at a concentration of 1M) was injected into a glove box filled with argon gas, and then the aluminum laminate bag was sealed to prepare a laminated lithium ion secondary battery (A).
[0372] (Example 5-2 to Comparative Example 5-3)
[0373] Laminated lithium ion secondary batteries (B) to (N) were prepared in the same manner as in Example 5-1 except that the negative electrode was changed to the one described in Table 6, and the rate characteristics and cycle characteristics were evaluated. The evaluation criteria are as follows.
[0374] (Evaluation criteria for rate characteristics)
[0375] 4 (excellent): more than 80%
[0376] 3 (Good): 70% or more and less than 80%
[0377] 2 (Acceptable): 60% or more but less than 70%
[0378] 1 (Not acceptable): Less than 60%
[0379] (Evaluation criteria for cycle characteristics)
[0380] 4 (excellent): more than 90%
[0381] 3 (Good): 85% or more and less than 90%
[0382] 2 (acceptable): 80% or more but less than 85%
[0383] 1 (Not acceptable): Less than 80%
[0384] (Example 5-31)
[0385] A laminated lithium ion secondary battery (C4) was produced in the same manner as in Example 5-1 except that a standard negative electrode was used instead of the negative electrode (A) and a positive electrode (C4) was used instead of the standard positive electrode.
[0386] (Example 5-32)
[0387] A laminated lithium ion secondary battery (C5) was produced by the same method as in Example 5-31 except that the positive electrode (C5) was used instead of the positive electrode (C4).
[0388] [Table 6]
[0389] Table 6
[0390]
[0391] In the embodiment described above, the following carbon nanotubes were used: pH 8.0-10.0, BET specific surface area 200 m 2 / g~800m 2 / g, when the fiber length (nm) of the carbon nanotube is set to Y and the BET specific surface area (μm) of the carbon nanotube is set to X, Y = -aX + b (a, b are constants, 2.2 ≦ a ≦ 3.5, 2300 ≦ b ≦ 5000). In the embodiment, compared with the comparative example, a lithium ion secondary battery with excellent rate characteristics and cycle characteristics can be obtained. Therefore, it is clear that the present invention can provide a lithium ion secondary battery with high capacity, high output and high durability that is difficult to achieve using existing carbon nanotubes and carbon nanotube dispersions.
[0392] In addition, in the comparative example, when the specific surface area is small, CNT (M) with a short fiber length or CNT (O) with a long fiber length cannot obtain a lithium ion secondary battery with excellent rate characteristics and cycle characteristics. It is believed that the reason is that the fiber length of CNT (M) is short, so the battery performance deteriorates due to the volume expansion of the active material accompanying the charge and discharge of the battery.
[0393] As mentioned above, although the present invention has been described with reference to the embodiments, the present invention is not limited to the above. Various changes that can be understood by those skilled in the art can be made to the structure and details of the present invention within the scope of the invention.
Claims
1. A carbon nanotube, characterized in that The following (1) to (3) are satisfied: (1) the pH of the carbon nanotube aqueous dispersion is 8.0 to 10.0; (2) the Buehr surface area of the carbon nanotube is 200 m 2 / g~800m 2 / g, (3) When the average fiber length of the carbon nanotubes is set to Y and the Buerter specific surface area of the carbon nanotubes is set to X, Y=-aX+b, wherein a and b are constants, 2.2≦a≦3.5, 2300≦b≦5000.
2. The carbon nanotube according to claim 1, characterized in that: In the Raman spectrum of carbon nanotubes, the 1560 cm -1 ~1600cm -1 The maximum peak intensity in the range of 1310 cm -1 ~1350cm -1 When the maximum peak intensity in the range of is set to D, the G / D ratio is 0.5 to 4.
5.
3. The carbon nanotube according to claim 1 or 2, characterized in that: The average outer diameter of carbon nanotubes is 5 nm to 20 nm.
4. The carbon nanotube according to any one of claims 1 to 3, characterized in that The volume resistivity of carbon nanotubes is 1.0×10 -2 Ω·cm~3.0×10 -2 Ω·cm. 5 . A carbon nanotube dispersion comprising the carbon nanotubes according to claim 1 , a dispersant, and an aqueous liquid medium.
6. The carbon nanotube dispersion according to claim 5, characterized in that: The complex elastic modulus of the carbon nanotube dispersion is 1Pa to 100Pa.
7. The carbon nanotube dispersion according to claim 5 or 6, characterized in that: The product X×Y of the complex elastic modulus X and the phase angle Y of the carbon nanotube dispersion is 100 or more and 1,500 or less.
8. The carbon nanotube dispersion according to any one of claims 5 to 7, characterized in that The dispersant is contained in an amount of 10 to 100 parts by mass based on 100 parts by mass of the carbon nanotubes.
9. The carbon nanotube dispersion according to any one of claims 5 to 8, characterized in that The pH is 7-11.
10. The carbon nanotube dispersion according to any one of claims 5 to 9, characterized in that The 50% particle size calculated by laser diffraction particle size distribution measurement is 1 μm to 20 μm.
11. The carbon nanotube dispersion according to any one of claims 5 to 10, wherein the carbon nanotube dispersion contains 0.4 parts by mass or more and 2.5 parts by mass or less of carbon nanotubes in 100 parts by mass of the carbon nanotube dispersion, wherein: When the viscosity of the carbon nanotube dispersion liquid measured at 6 rpm using a Brookfield viscometer is α and the viscosity of the carbon nanotube dispersion liquid measured at 60 rpm is β, α / β satisfies 2.0≦α / β≦6.
0. 12 . A carbon nanotube resin composition comprising the carbon nanotube dispersion according to claim 5 , and a binder resin.
13. The carbon nanotube resin composition according to claim 12, characterized in that: The binder resin includes at least one selected from the group consisting of carboxymethyl cellulose, styrene butadiene rubber, and polyacrylic acid. 14 . A composite material slurry comprising the carbon nanotube resin composition according to claim 12 or 13 and an active substance.
15. An electrode film, which is a coating film of the composite material slurry according to claim 14. 16 . A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein at least one of the positive electrode or the negative electrode comprises the electrode film according to claim 15 .
17. A non-aqueous electrolyte secondary battery comprising the carbon nanotube according to any one of claims 1 to 4.
18. A vehicle comprising the nonaqueous electrolyte secondary battery according to claim 16 or 17.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP1992155776A
Nonaqueous electrolyte secondary battery
JP1992237971A
Negative electrode material and secondary battery using the same
JP2004178922A
Carbon nanotube-dispersed polar organic solvent and method for producing the same
JP2005162877A
Aqueous dispersion of carbon nanotube, electroconductive composite, and method for producing the same
JP2010254546A